African American actresses : the struggle for visibility, 1900-1960 - Regester, Charlene B., 1956- (Indiana University Press, 2010)
Nine actresses, from Madame Sul-Te-Wan in Birth of a Nation (1915) to Ethel Waters in Member of the Wedding (1952), are profiled in African American Actresses. Charlene Regester poses questions about prevailing racial politics, on-screen and off-screen identities, and black stardom and white stardom. She reveals how these women fought for their roles as well as what they compromised (or didn't compromise). Regester repositions these actresses to highlight their contributions to cinema in the first half of.